Pengaruh Pemberian Urin Sapi Yang Difermentasi Terhadap Pertumbuhan dan Produksi Tanaman Sawi Hijau (Brassica rafa) - Karya Rizki; Aslim Rasyad; Murniati ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
Green mustard is its broadleaf vegetable crops that is economically potential because of its high demand . Increased production have tended to use inorganic fertilizers and pesticides excessive. In the now widely circulated one organic fertilizer is cow urine. Giving cow urine on the ground to improve the nature of the soil chemistry, soil physics and biological properties of soil. This research was conducted at the Experiment Unit of the Faculty of Agriculture, University of Riau from April to May 2013. Field levels of experimental was arrangenina completely randomized design consisting of 5 fermented cow urine lei U0 : no cow urine, U1 : cow urine 100 ml/l of water, U2 : cow urine 200 ml/l of water, U3 : cow urine 300 ml/l of water, U4 : cow urine 400 ml/l of water. Observations were plant height, leaf number, leaf area, root volume, fresh weight per plant and fresh weight of plant per plot. Application of fermented cow urine to the plant improve palnt growth and all yield components except root volume. Increasing the concentration of fermented cow urine teut to increas crop production. Giving fermented cow urine at concentration of 20% - 40% gives the growth and yield of mustard plant better. Keyword : Mustar green, Cow urine